The war criminal's son : the civil war saga of William A. Winder - Singer, Jane, 1947- (Potomac Books, an imprint of the University of Nebraska Press, 2019)
"The hitherto unknown saga of Union Captain William Andrew Winder and his father Confederate General John H. Winder, who both served as prison commandants during the Civil War, becoming blood-sworn enemies"--